Apakah Perekayasaan Laba Dipengaruhi oleh Akuntansi Lingkungan, Kapitalisasi Pasar, dan Asimetri Informasi? - Bahtiar Effendi (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to examine the effect of the quality of environmental accounting disclosures, good corporate governance, and information asymmetry on the level of discretionary accruals. The specific target of this research is to empirically examine the effect of the quality of environmental accounting disclosures, good corporate governance, and information asymmetry on the level of discretionary accruals. The population of this research is all mining sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period as many as 47 companies. Determination of the sample was selected based on the Slovin method and purposive sampling criteria with a quantitative descriptive approach. This study uses secondary data from company financial reports, company annual reports and sustainability reports. Data analysis was performed using multiple linear regression analysis using SPSS version 26.0. By using multiple linear regression analysis as a research method, the results show that partially the quality of environmental accounting disclosures, good corporate governance, and information asymmetry have a significant effect on the level of discretionary accruals. Furthermore, based on the results of simultaneous testing, it is found that the quality of environmental accounting disclosures, good corporate governance, and information asymmetry together have a significant effect on the level of company discretionary accruals.